English for Business Communication. A Modular Short Course on Socialising, telephoning, Presenting, Meeting, and Negotiating. Students Book. - Sweeney, Simon (Cambridge Cambridge University Press, 1997)
English for Business Communication is a short course for intermediate level students who need to improve their communicative ability when: socilising, telephoning, presenting, taking part in meetings, and negotiating.
Keywords: Business English